Content of Trace Elements and Human Health Risk Assessment via Consumption of Commercially Important Fishes from Montenegrin Coast - Neda Bošković; Danijela Joksimović; Oliver Bajt (Foods, 2023)
Muscle tissues of Mullus barbatus and Merluccius merluccius were analyzed for the presence of selected trace elements (As, Hg, Cd, and Pb) to determine the value of the daily intake of trace elements from fish consumption and to assess the risk to human health. The mean concentrations of As in the muscle tissue of M. barbatus and M. merluccius for the entire period were 19.689 mg/kg wet weight (ww) and 8.356 mg/kg ww, Hg 0.497 mg/kg ww and 0.153 mg/kg ww, and Pb 0.031 mg/kg ww and 0.025 mg/kg ww, respectively. The concentrations of Cd in all fish sampled were below the detection limit (<0.02 mg/kg ww). The evaluation of the potential health risk assessments based on the target hazard quotient (THQ) and estimated daily intake (EDI) indicated that the intake of As in both fish species and Hg for M. barbatus could pose an appreciable risk to human health. The calculated hazard index (HI) was higher than 1 for both fish species. The continuous monitoring of trace elements’ concentrations in fish is strongly recommended, as the results demonstrate potential health risks due to the presence of As and Hg.